Organizational Citizenship Behavior as Mediator: Competence and Commitment Effects on Performance - Tri Hapsari Ni Komang; Kepramareni Putu; Dwi Puspitawati Ni Made; Suardhika I Nengah (International Journal of Applied Business and International Management, 2025)
The performance of public service agencies, such as the Regional Disaster Management Agency (BPBD) of Badung Regency, plays a crucial role in ensuring community satisfaction. Recent declines in the public satisfaction index have raised concerns over employee competence and commitment. This study examines the influence of competence and organizational commitment on employee performance, with organizational citizenship behavior (OCB) as a mediating variable. Using a quantitative approach and a census method, data were collected from 85 BPBD employees and analyzed with Partial Least Squares (SmartPLS 4). The results show that competence (? = 0.398, t = 3.664, p 0.001) and commitment (? = 0.272, t = 2.798, p 0.001) significantly improve performance. Both competence (? = 0.506) and commitment (? = 0.399) positively influence OCB, which in turn significantly enhances performance (? = 0.269, t = 2.841, p = 0.005). Mediation testing confirms that OCB partially mediates the effects of competence (? = 0.136, p = 0.029) and commitment (? = 0.107, p = 0.015) on performance. These findings highlight the importance of fostering OCB to maximize the positive impact of competence and commitment on service quality